LncRNA AFAP1-AS1 Promotes Oral Squamous Cell Carcinoma Development by Ubiquitin-Mediated Proteolysis - Bao-Jun Li; Feng-Hai Ren; Cui Zhang; Xing-Wei Zhang; Xiao-Hui Jiao (Elsevier, 2024)
Background and purpose: Long noncoding RNA (lncRNA) dysregulation has been reported to play a pivotal role in the development of cancers. In this study, we aimed to screen the key lncRNA in oral squamous cell carcinoma (OSCC) via bioinformatics analysis and further validate the function of lncRNA in vitro and in vivo. Methods: Bioinformatics analysis was conducted to identify differentially expressed lncRNAs between control and OSCC samples. Quantitative real-time-polymerase chain reaction was employed to detect the expression of differentially expressed lncRNAs in human tongue squamous cell carcinoma and human oral keratinocytes cell lines. The biological function of lncRNA and its mechanism were examined via the experimental assessment of the cell lines with the lncRNA overexpressed and silenced. Additionally, to further explore the function of lncRNA in the progression of OSCC, xenograft tumour mouse models were established using 25 mice (5 groups, each with 5 mice). Tumour formation was observed at 2 weeks after the cell injection, and the tumours were resected at 5 weeks post-implantation. Results: Two lncRNAs, LINC00958 and AFAP1-AS1, were found to be correlated with the prognosis of OSCC. The results of the quantitative real-time-polymerase chain reaction indicated that the 2 lncRNAs were highly expressed in OSCC. In combination with the previous literature, we found AFAP1-AS1 to be a potentially important biomarker for OSCC. Thus, we further investigated its biological function and found that AFAP1-AS1 silencing inhibited cell proliferation, migration, and invasion whereas AFAP1-AS1 overexpression reversed the effect of AFAP1-AS1 silencing (P < .05). Mechanism analysis revealed that AFAP1-AS1 regulated the development of OSCC through the ubiquitin-mediated proteolysis pathway. Conclusions: AFAP1-AS1 is an oncogene that aggravates the development of OSCC via the ubiquitin-mediated proteolysis pathway. It also provides a novel potential therapy for OSCC.